Desenvolvimento de catalisadores modificados com Sn suportado em materiais à base de sílica, do tipo Magadiíta, para conversão de biomassa em potenciais produtos químicos de interesse industrial - Santos, Tiago Gomes dos (2020)
Magadiites constitute an important class of lamellar silicates, in which the negative charges can be compensated by either Na+ or H+ located in the interlayer spaces, resulting in a cluster of spheres. The introduction of cations in the interllamelar spacing or in silicate layers plays an important role in modulating the material properties. In this work, stannosilicates were hydrothermally synthesized via the isomorphic substitution of Si by Sn in the structure of magadiite using two different sources of Sn (Na2SnO3 or SnCl4·5H2O) to investigate the influence of the nature of the precursor on the characteristics of the final material, which can be promised in the catalysis are. Samples synthesized with various Sn/Si molar ratios were characterized by several techniques, and regardless of the Sn source used, the results confirm the presence of tetrahedral SnO4 species on Sn-magadiite lamellae, giving highly crystalline materials that exhibit weak to moderate acidity. It is important to highlight that usually SnCl4·5H2O is used as a source of tin, and to our knowledge, this study is the first to use the precursor Na2SnO3 as a promising and cheap Sn source for the synthesis of this type of stannosilicate, leading to materials with high crystallinity but slight morphological differences due to the formation of cauliflower structures on the lamellae. Regarding the catalytic study of these materials, they presented the ability to convert ᴅ-fructose into aqueous medium with high activity and selectivity producing a spectrum of different products of industrial importance, including the formation of 5-HMF and lactic acid that are among the 12 most promising molecules derived from sugars. Specifically, catalytic systems achieved a conversion of up to 89 % at 6 h and yield of ≤70 % in 2 h reaction to 150 °C. In general, catalysts with Sn were preferred for retro-aldolic fragmentation reactions, especially pyruvaldehyde and lactic acid reaching maximum selectivity of 38 and 27 % to 150 °C, respectively. However, a decay was observed in the formation of carbonyl compounds by the retro-aldolic route due to the increase in the Sn/Si ratio, which followed alternative reaction pathways. However, the data presented in this study showed that heterogeneous catalysis can play a fundamental role in the development of green processes, with lower energy expenditures and selectively generating high value-added products from derived from biomass. At the same time, they can strengthen and expand the use of renewable sources to obtain chemical and energy inputs, aiming to consolidate a sustainable industrial segment.